Treatment of clinically amyopathic dermatomyositis. (3rd December 2018) - Callander, J.; Robson, Y.; Ingram, J.; Piguet, V.
Summary: Dermatomyositis is an unusual auto‐immune condition (where the body's immune system doesn't function correctly) where a characteristic rash is associated with muscle inflammation. However, some patients have the skin disease without associated muscle disease, which is called amyopathic dermatomyositis, and there is no set agreement about the best way to treat these patients. The authors, based in Cardiff, Wales, reviewed the literature concerning the treatment of patients with amyopathic dermatomyositis. They identified eighteen case series (information from more than one patient) and 42 case reports (information from just one patient), but no randomised controlled trials, which are the gold‐standard of research. Antimalarials, such as hydroxychloroquine, were most commonly used, but ineffective in 55% of patients. Other drugs included topical and systemic corticosteroids, methotrexate, dapsone, mycophenolate mofetil and topical tacrolimus. Intravenous immunoglobulin led to improvement or even remission in the greatest number of patients with dermatomyositis with or without muscle involvement. The authors emphasise the need for more robust, unbiased studies to assess the efficacy of treatment in this condition. Abstract : Linked Article:  Callander et al. Br J Dermatol 2018;179 :1248–1255